Le témoignage de la parenté : la mémoire généalogique dans les dispenses matrimoniales à Florence (xve-xvie siècles) - Jasmin Hauck (Genre & Histoire)
This article is based on a source that has been so far rather neglected when studying the genealogical memory: the witness accounts given by kin couples that were connected up to the 4th canonical degree which they had to provide ecclesiastical courts with in order to prove a kinship tie and thus obtain a matrimonial dispensation. Starting from late medieval Florentine sources, we developed a new method of graphically representing the genealogical memory. This new tool will be used to interrogate the gendered representation of the ancestors in the genealogical trees drawn by the notaries in charge of recording the procedure. Finally, for the cases where we know the exact kinship link that connects witnesses and supplicants we pose the question whether the distribution of male and female ancestors, that connect the supplying couples, did have an impact on the choice of specific witnesses. In other words, do these witnesses chosen for procedure occupy preferential genealogical positions that facilitate their memory of certain ancestors? Thus, is the witness choice based on an – assumed or real – greater difficulty to remember female rather than male ancestors?